HEALT PREVENTION : OVERVIEW OF PARENTS' KNOWLEDGE AND ATTITUDE ABOUT DIARRHEA DISEASE IN THE CHILDREN'S POLY PARIAMAN HOSPITAL - Aulia Asman and An Autika Asman (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2022)
The incidence of diarrhea is not less than one billion episodes every year worldwide, 25-35 million of which occur in Indonesia. Each child under five experiences diarrhea two to eight times each year with an average of 3.3 times. From the results of the Pariaman Hospital medical record report, cases of diarrhea treated from January to August 2018 recorded 108 patients and diarrhea cases who visited the pediatric polyclinic from January to October 2017 recorded as many as 82 sufferers. The purpose of the study was to see how the knowledge and attitudes of parents about diarrheal disease at the Children's Poly Hospital of Pariaman Hospital were described. Diarrhea is an excessive loss of fluids and electrolytes that occurs due to the frequency of one or more bowel movements in the form of watery/liquid stools. The causes of diarrhea are infection factors, malabsorption factors, food factors, psychological factors. This research uses a descriptive method. This research was conducted on February 02 to February 09, 2018 at the children's poly hospital Pariaman. The target of this study were all parents who visited the children's polyclinic of RSUD Pariaman during the research period. A sample of 30 respondents using the Accidental Sampling technique. The data is processed using manual methods. From the results of the study in general, it shows that of the 30 respondents, who have low knowledge 56.7%, 63.3% have a negative attitude. Knowledge and attitude variables are a description that causes low knowledge and attitudes of parents at the Children's Poly Hospital Pariaman in 2018. It is hoped that parents can increase knowledge about diarrhea which is useful for reducing the incidence of diarrhea and increasing attitudes towards diarrheal disease, and immediately go to the hospital. or other health services if diarrhea occurs. It is also recommended for health care workers to play an active role in providing information and counseling about diarrhea.